IMPROVING THE REPORTING OF FINANCIAL RESULTS IN ACCORDANCE WITH INTERNATIONAL STANDARDS - Misirov Komoliddin Mamasabirovich (Antis Publisher, 2024)
It is regulated by parallel accounting and transformation of financial statements which are based on national standards and they are in accordance with international standards in our Republic. Therefore, it is advisable to make proposals for the preparation of financial statements in accordance with international standards and increase investor confidence, while reducing costs and increasing the transparency of financial statements